Association of OSTA index with bone mineral density (BMD) and its comparison with calcaneal quantitative ultrasound for the prediction of low BMD in peri-menopausal Indian women - Patel, Sachin M.; Jadhav, Pradeep R.; Vieira, Alfven (International Journal of Research in Medical Sciences, 2017)
Background: Osteoporosis is characterized by low bone mineral density (BMD) and an increased risk of fractures with advancing age in postmenopausal women. BMD measurements with dual energy X-ray absorptiometry (DEXA) are costly and not widely available The Osteoporosis Self-Assessment Tool for Asians (OSTA) index is a simple tool based on age and body weight to predict low BMD and identify women at risk of osteoporosis. The objective was to study the association of OSTA index with BMD (T-score) and to validate OSTA index in comparison with calcaneal Quantitative Ultrasound (QUS) for the prediction of low BMD in peri-menopausal Indian women. Methods: This was a prospective, cross-sectional, descriptive study carried out in department of physiology of a tertiary care teaching hospital (Navi Mumbai). Seventy two peri-menopausal women between 40 to 55 years with no previous diagnosis of osteoporosis were included. Participants’ socio-demographic detail, anthropometric measurements, OSTA index and QUS-based BMD was recorded. Pearson’s correlation test was used. Sensitivity, specificity, positive and negative predictive value was calculated. Results: OSTA index did not correlate with BMD in the entire samples. On subgroup analysis, OSTA index significantly correlated in a positive direction with BMD (T-score) in women in the age group of 50-55 years. OSTA index had a sensitivity of 70 %, and specificity of 84.62 % at T-score cutoff value of < -1. Conclusions: OSTA index is a simple risk assessment tool that can be used to identify women with low BMD in the age group of 50-55 years.